Investigation of Physical Education and sports teachers' job satisfaction levels - Sief Addeen Ra’ed Alkafaween; Oğuzhan Yüksel; Piyami Çakto; Gökçe Çimen Binkuyu; Orhan Demir; Aybüke Yaprakcı (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Objectives: The aim of this study is to examine the job satisfaction levels of physical education and sport teachers according to various variables.